A study on knowledge of breast feeding and effect of antenatal counselling on exclusive breast feeding in primigravida mothers - Tiwari, Kamlesh; Savarna, Neha; Khanam, Ishmat (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Exclusive breastfeeding up to 6 months of age is very beneficial not only to baby and mothers, but also to the family, society and the whole nation. In spite of best efforts by various organizations at government and NGO levels, the counselling for breast feeding during ante natal period is almost an unaddressed arena, which if proper attention is given, may result in very high incidence of successful breast feeding. Methods: It is a hospital based prospective study. A total of 150 primiparous mothers (100 study group and 50 control group) were counselled during every antenatal checkup for exclusive breast feeding attending the OPD of Obstetrics & Gynaecology department of Vardhman Institute of Medical sciences, Pawapuri, Nalanda, Bihar from January 2015 to December 2016 and the outcome of counselling was observed during follow up in puerperium for 6 weeks. Results: Similar profile primiparous mothers in both study and control group, the mothers who were counselled on their antenatal visit for exclusive breast feeding, the success rate was much higher in counselled group than study group (p value 0.0001). It was also observed that the prior information about breast feeding were provided by electronic media, papers and family members and in this regard contribution of health system is minimal. Conclusions: Every obstetrician and other care givers must include routine care of breast and counselling on breast feeding during antenatal check up to enhance the confidence of primiparous mothers. A few extra minutes spared in counselling on breast feeding has a long-lasting effect on successful breast feeding during the post-natal period.